Perilaku caring perawat terhadap kepuasan pasien di UPT Puskesmas rawat inap - Triyoso Triyoso; Martina Sari (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2020)
Nurse caring behaviors and patient satisfaction: The impact of patients experience at Bukit Kemuning inpatient public health centreBackground: The results of the pre-survey conducted on January - 2019 based on the medical records of the Bukit Kemuning Inpatient Health Center in North Lampung recorded in 2018 had of 279 inpatients. Base on evaluation in Bukit Kemuning Inpatient Health Center, the Minimum Service Standards (MSS) achievement scored of 67.29% describes the service quality is still suboptimal.Purpose: Knowing relationship between nurses' caring behavior towards patient satisfaction in Bukit Kemuning Inpatient Health Centre North Lampung RegencyMethod: A quantitative cross-sectional approach, the population of all outpatient who had experienced hospitalization at Bukit Kemuning Inpatient Health Center, with a sample of 282 respondent. The variables of this study were nurse caring behavior and patient satisfaction. The research conducted at the Bukit Kemuning Inpatient Health Center UPT North Lampung Regency. data collection using a questionnaire. Data analysis was univariate and bivariate (chi square).Results: Knowing the respondents' statement that nurses' shown caring behavior in a poor category of 162 (57.4%), patients unsatisfied of 140 (49.4%), There is a relationship between Nurse caring behaviors and patient satisfaction at Bukit Kemuning inpatient public health centre North Lampung Regency (p-value = 0.000 OR = 4.659)Conclusion: There is a correlation between Nurse caring behaviors and patient satisfaction: The impact of patients experience at Bukit Kemuning inpatient public health centre, for the Health Center management to consider for nurses' staff for conducting caring behavior training and improve health services.Keywords: Nurses; Caring behavior; Patient; SatisfactionPendahuluan: Standar kepuasan pasien di pelayanan kesehatan ditetapkan secara nasional oleh Departemen Kesehatan. Hasil pra survey yang dilakukan tanggal 5 – 9 Januari 2019 berdasarkan data rekam medis Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara tercatat tahun 2018 jumlah pasien yang melakukan kunjungan rawat jalan sebesar 11.169 orang dan rawat inap sebanyak 279 orang. Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara Standar SPM > 90 % dengan hasil capaian hanya 67, 29% sehingga dapat menggambarkan mutu pelayanan masih belum optimal.Tujuan : Diketahui hubungan perilaku caring perawat terhadap kepuasan pasien di UPT Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara tahun 2019Metode: Penelitian kuantitatif pendekatan Cross Sectional, populasi seluruh pengunjung Puskesmas, dengan sampel berjumlah 282 orang Objek dalam penelitian ini adalah perilaku caring perawat dan kepuasan pasien. Penelitian dilakukan di UPT Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara. bulan Januari – Juni 2019 . pengumpulan data menggunakan kuesioner. Analisis data secara univariat dan bivariat (chi square).Hasil: Diketahui pernyataan responden tentang perawat yang menunjukkan perilaku caring kategori buruk, sebesar 162 (57,4%) responden, kepuasan keluarga pasien kurang puas, sebesar 140 (49,4%) responden, Ada hubungan antara perilaku caring perawat terhadap tingkat kepuasan keluarga pasien di UPT Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara tahun 2019 (p-value=0,000,0,05, OR=4,659)Simpulan: Ada hubungan antara perilaku caring perawat terhadap tingkat kepuasan keluarga pasien di UPT Puskesmas Rawat Inap Bukit Kemuning Kabupaten Lampung Utara tahun 2019, bagi pihak manajemen Puskesmas sebagai bahan pertimbangan untuk mengadakan pelatihan perilaku caring perawat guna meningkatkan pelayanan pasien.